Clinicopathological and molecular significance of HER2-low expression in Asian women with triple-negative breast cancer - Cuiyan Yang; Haoyu Wang; Yiwei Tong; Zheng Wang; Xi Sun; Anqi Li; Yujie Lu; Mengyuan Han; Siji Zhu; Lei Dong; Kunwei Shen; Xiaosong Chen (Therapeutic Advances in Medical Oncology, 2025)
Background: Heterogeneity of human epidermal growth factor receptor 2 (HER2) expression exists in triple-negative breast cancer (TNBC). The evolution of the HER2 testing algorithm has led to the new classification of the HER2-low category, with unclear clinicopathological and molecular features in Asian women with HER2-low TNBC. Objectives: This study aimed to assess the clinicopathological and molecular characteristics of HER2-low TNBC in Asian women. Design: Our study prospectively included 3376 patients with TNBC diagnosed from 2009 to 2021 in the Shanghai Jiao Tong University Breast Cancer Database (a multicenter dataset), and 92 patients from The Cancer Genome Atlas (TCGA) cohort were enrolled. Methods: Two different independent TNBC cohorts were included, a multicenter cohort (Whole cohort, n  = 3376) and the TCGA cohort ( n  = 92). Genomic profiling covering 32 mutations for Homologous Recombination Repair and other cancer predisposition genes was obtained. Clinicopathological features, genomic status of the above genes, treatment response, and disease prognosis were compared between HER2-low and HER2-zero TNBC patients. Results: In Asian females, 1611 (47.72%) TNBC patients were HER2-low. HER2-low was associated with a higher percentage of postmenopausal status (odds ratio (OR) = 1.64, p  < 0.001), lymph node positivity (OR = 1.14, p  = 0.003), and invasive ductal carcinoma histology (OR = 1.21, p  = 0.012). HER2-low group had less BRCA1 mutation (7.02% vs 13.76%, p  = 0.038) but was associated with a higher rate of PIK3CA mutation (28.07% vs 12.17%, p  < 0.001) compared with HER2-zero TNBC. No significant difference in breast pathologic complete response rate, breast cancer-free interval, or overall survival was observed between HER2-low and HER2-zero TNBC. In the TCGA cohort, lipid metabolism genes were upregulated in the HER2-low TNBC, enriched in alpha-linolenic acid metabolism (normalized enrichment score = 1.51, p  = 0.019). Conclusion: Our results show that HER2-low TNBC had specific clinicopathological, genomic profiling, and biological features compared with HER2-zero TNBC in Asian women, but without significant differences in treatment response and prognosis, warranting exploring better treatment strategies to improve disease outcomes.